CURRENT ASPECTS OF CYTOLOGICAL SCREENING FOR CANCER OF THE CERVIX UTERI: A REVIEW - L. E. Komarova (Опухоли женской репродуктивной системы, 2014)
More than 500,000 cases of cervix uteri cancer are annually registered in the world. Almost half die within the first year due to its late diagnosis. In this connection, the early diagnosis of cancer is a challenge today.